The Interaction Effect of Nomination Committee’s Effectiveness on Board of Directors’ Characteristics and Firm Performance - Mujeeb Saif Mohsen Al-Absy; Nada Hameed AlMahari (Administrative Sciences, 2023)
This study aimed to examine the interaction effect of the nomination committee’s effectiveness on the board of directors’ characteristics and firm performance (measured by return on assets and earnings per share). The nomination committee was scored for committee separation, size, independence, meeting frequency, and the number of female directors. The study selected all listed firms on the Bahrain Bourse for two years, 2020 and 2021, using ordinary least-squares regression to examine the relationship. The results showed that the interaction of the nomination committee with some characteristics of the board of directors had a significant impact on firm performance. With the interaction of the nomination committee, board meeting frequency became significantly positively associated with firm performance as measured by return on assets and earnings per share, as opposed to the insignificant results found in the direct relationship. Similarly, with the interaction of the nomination committee, the number of female directors became more significantly positively associated with firm performance using the measurement of return on assets, while it became significantly positively associated with firm performance using earnings per share, compared to an insignificant positive impact found in the direct relationship. The results show that there is a need to re-evaluate the role of the board of directors and strengthen its effectiveness. This study is the first to alert policymakers, businesses and their stakeholders, and researchers to the significance of having an effective nomination committee, which could play an important role in enhancing the board of directors’ effectiveness and hence firm performance. It makes a significant contribution to the literature by providing empirical evidence on the interaction impact of NC (as a score) on BOD characteristics and firm performance.